The Alchemy of Empire : Abject Materials and the Technologies of Colonialism. - Sudan, Rajani (Fordham University Press, 2016)
The Alchemy of Empire unravels the non-European origins of Enlightenment science. Focusing on the abject materials of empire-building, this study traces the genealogies of substances like mud, mortar, ice, and paper, and forms of knowledge like inoculation, arguing that East India Company employees deployed the paradigm of alchemy in order to make sense of the new worlds they confronted.